2020
DOI: 10.3389/fonc.2020.574208
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Contactin 1 in Cancers: What We Know So Far

Abstract: Cancers are among the difficult-to-treat diseases despite advances in diagnosis and treatment. Although newer effective targets remain to be discovered, targeted therapy has emerged as a promising field. In the last decade, contactin 1 (CNTN1) has surfaced as an important cancer-related molecule. CNTN1 is a neuronal membrane glycoprotein, which, if overexpressed, is found in different cancer cell lines, cancer tissues, and transgenic mice. It is positively associated with lymphatic invasion, metastasis, late T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Contactin1 ( Cntn -1 ) is a cell adhesion neuronal membrane glycoprotein belonging to the immunoglobulin superfamily. The protein has been shown to utilize EMT-dependent promotion for enhanced cell invasion, migration, and metastasis in several different types of carcinoma [ 43 ]. Downregulation of Cntn-1 resulted in decreased activity of the PI3K/Akt signaling and docetaxel resistance in PCa cells lines and xenografts [ 44 ].…”
Section: Mouse Model and In Vitro Studies Of Emt In Pcamentioning
confidence: 99%
“…Contactin1 ( Cntn -1 ) is a cell adhesion neuronal membrane glycoprotein belonging to the immunoglobulin superfamily. The protein has been shown to utilize EMT-dependent promotion for enhanced cell invasion, migration, and metastasis in several different types of carcinoma [ 43 ]. Downregulation of Cntn-1 resulted in decreased activity of the PI3K/Akt signaling and docetaxel resistance in PCa cells lines and xenografts [ 44 ].…”
Section: Mouse Model and In Vitro Studies Of Emt In Pcamentioning
confidence: 99%
“…The altered CNTN1 expression in the intercellular adhesive properties of cancer cells certainly plays a role in tumorigenesis. CNTN1 promotes an adhesion switch during the epithelial‐to‐mesenchymal transition that is associated with cancer invasion by elevating PI3K/AKT and NOTCH signalling pathways 53,54 . It was proved that CNTN1 acts as a downstream effector of the VEGF‐C/VEGFR3 signalling pathway in cancer cells 55 .…”
Section: Discussionmentioning
confidence: 99%
“…CNTN1 promotes an adhesion switch during the epithelial-to-mesenchymal transition that is associated with cancer invasion by elevating PI3K/AKT and NOTCH signalling pathways. 53,54 It was proved that CNTN1 acts as a downstream effector of the VEGF-C/VEGFR3 signalling pathway in cancer cells. 55 CNTN1 was also confirmed to be regulated by the Wnt signalling, Hedgehog signalling, and calcium signalling pathways by KEGG analysis.…”
Section: F I G U R E 8 Correlation Analysis In Different Algorithms B...mentioning
confidence: 99%
“…CNTN -1, located on chromosome 12q11-q12 and a neuronal cell adhesion molecules of the immunoglobulin superfamily, participates in nervous system development ( Su et al, 2006 ). Additionally, CNTN -1 was also reported to promote the malignant progression of cancer cells as a downstream molecule of the VEGF-C/Flt-4 axis ( Zhou et al, 2015 ; Liang et al, 2020 ). In our previous studies, CNTN -1 expression was found to be positively correlated with lymphatic invasion of lung adenocarcinoma patients who received adjuvant cisplatin- or carboplatin-based treatment after surgery ( Chen et al, 2015 ), suggesting that the CNTN -1 upregulation may be induced by platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%